Good Governance Principles in The Implementation of Public Service Innovation Policies In Kubu Raya Regency - Maryuni, Sri (Iapa Proceedings Conference, 2024)
The Kubu Raya Public Service Mall has implemented good governance principles in implementing public service innovation policies. This effort aims to provide maximum service to the community by facilitating the people of Kubu Raya Regency in handling administrative matters from various government agencies. The research conducted is descriptive and uses qualitative analysis techniques to describe the process of applying good governance principles in the implementation of public service innovation policies in Kubu Raya Regency. This includes cognitive capabilities that must be possessed by public organizations in dynamic governance, such as thinking ahead, thinking again, and thinking across. The results of the research indicate that the services provided at the Kubu Raya Public Service Mall are based on people's real needs, rather than just administrative decisions. The establishment of the Kubu Raya Public Service Mall is a complex process that requires collaboration, commitment, continuous evaluation, and adaptation to existing challenges. However, the process of applying good governance principles in the implementation of public service innovation policies still faces some challenges. These challenges include limited delivery of information related to the Kubu Raya Public Service Mall, which has led to a lack of awareness and understanding of the purpose of the Public Service Mall among many people. Additionally, the provision of limited counters has caused some services to be available only on certain days, and some agencies have had to use other facilities as service counters.